2004
DOI: 10.1016/j.molcel.2004.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Rvb1p/Rvb2p Recruit Arp5p and Assemble a Functional Ino80 Chromatin Remodeling Complex

Abstract: The Rvb1p and Rvb2p (or TIP48 and TIP49) nuclear ATP binding proteins are universally conserved in eukaryotes and essential for viability of yeasts. Rvbp associate with each other as a double hexamer, with YHR034c and with two complexes involved in chromatin remodeling, Ino80.com and Swr1.com. Loss of Rvb1p or Ino80p affects many yeast promoters similarly. Rvbp are not essential for the recruitment of Ino80p to promoters but are essential for the catalytic activity of Ino80.com. Loss of Rvbp leads to loss of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
214
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 188 publications
(223 citation statements)
references
References 36 publications
9
214
0
Order By: Relevance
“…Several other global gene expression profiling experiments also showed that the INO80 complex regulates a specific set of gene both negatively and positively [9,47]. Two phosphate regulated genes, PHO5 and PHO84 were used to study the promoter regulation mechanism of INO80, and it was found that INO80 had a repressive effect on the PHO5 promoter and a stimulatory effect on the PHO84 promoter, suggesting that INO80 is required for proper regulation of these promoters [17]. Furthermore, in vitro transcription assays show a 10 fold increase in transcriptional activation of chromatin remodeled by INO80.com [8].…”
Section: Ino80com Functionsmentioning
confidence: 99%
See 4 more Smart Citations
“…Several other global gene expression profiling experiments also showed that the INO80 complex regulates a specific set of gene both negatively and positively [9,47]. Two phosphate regulated genes, PHO5 and PHO84 were used to study the promoter regulation mechanism of INO80, and it was found that INO80 had a repressive effect on the PHO5 promoter and a stimulatory effect on the PHO84 promoter, suggesting that INO80 is required for proper regulation of these promoters [17]. Furthermore, in vitro transcription assays show a 10 fold increase in transcriptional activation of chromatin remodeled by INO80.com [8].…”
Section: Ino80com Functionsmentioning
confidence: 99%
“…It has been shown that ino80 null mutants exhibited decreased gene activation mediated by a UAS element, ICRE (inositol/choline-responsive element), and pleiotropic expression defects [12]. In a microarray assay, it was found that 150 out of 5602 yeast genes showed at least 2 fold change in mRNA level upon acute removal of INO80, with roughly equal numbers of up regulated and down regulated genes [17]. Several other global gene expression profiling experiments also showed that the INO80 complex regulates a specific set of gene both negatively and positively [9,47].…”
Section: Ino80com Functionsmentioning
confidence: 99%
See 3 more Smart Citations